Unveiling the chemical composition of unique flavor profiles in raw Pu-erh tea from different Tea-Producing Mountains - Xinyi Zhang; Hongyu Chen; Yang Liu; Xingchang Ou; Lun Liu; Jian Ouyang; Ronggang Jiang; Xiaoqin Yi; Ligui Xiong; Jianan Huang; Zhonghua Liu (Food Chemistry: X)
The Chinese proverb “One mountain, one flavor” reflects that raw pu-erh tea (RPT) from different tea-producing mountains (TPMs) possesses distinct flavor profiles. However, limited research has been conducted on the chemical composition underlying distinct flavor profiles. In this study, sensory evaluation and main phytochemical compositions revealed diverse aromas of RPTs from 26 TPMs. A total of 225 volatile compounds were analyzed qualitatively and quantitatively by comprehensive two-dimensional gas chromatography time-of-flight mass spectrometry, including hydrocarbon compounds, ketones, alcohols, and aldehydes. Furthermore, twenty-one common key odor-active compounds, potentially influencing the regional flavor, were identified by gas chromatography-olfactometry and odor activity value. Multivariate statistical analysis showed that geographical factors—longitudes, latitudes, counties, and elevations—account for 37.02 % of the aroma profile variance, implying the possible influence of other potential factors. The study results serve as a reference for a better understanding of the correlation between the RPT flavor characteristics and geographical attributes in TPMs.